GUI Application to Setup Simple Graph on the Plane using Tkinter of Python - Sumual, Gery Josua; Pinontoan, Benny; Latumakulita, Luther A. (d'CARTESIAN:Jurnal Matematika dan Aplikasi, 2021)
In graph theory, drawing a simple graph on the plane might result an intersection of pair of edges that is not intended as a vertex called crossing. The least amount of crossing in any simple drawing of a graph is the crossing number of that graph, ð‘ð‘Ÿ(ðº). Given a graph G and an integer ð¾, the general problem to proof ð‘ð‘Ÿ(ðº) â‰¤ ð¾ is an NP-Complete problem, which means, it is likely intractable. One of the way to proof ð‘ð‘Ÿ(ðº) â‰¤ ð¾ is by showing the drawing of graph ðº with ð¾ number of crossing; doing it with a computer application can be much of help. Therefore, the purpose of our research is to create one using Tkinter of Python. The development of the application is feature driven. The developed features are used to find any simple drawing of graphs on the plane. As the result, the application can proof ð‘ð‘Ÿ(ð¾_3,3) â‰¤ 1,Â ð‘ð‘Ÿ(ð¾_6) â‰¤ 3, andÂ ð‘ð‘Ÿ(ð¾ðº_5,2) â‰¤ 2.